2003
DOI: 10.1073/pnas.232711199
|View full text |Cite
|
Sign up to set email alerts
|

CEACAM1-4S, a cell–cell adhesion molecule, mediates apoptosis and reverts mammary carcinoma cells to a normal morphogenic phenotype in a 3D culture

Abstract: In a 3D model of breast morphogenesis, CEACAM1 (carcinoembryonic antigen-related cell adhesion molecule 1) plays an essential role in lumen formation in a subline of the nonmalignant human breast cell line (MCF10A). We show that mammary carcinoma cells (MCF7), which do not express CEACAM1 or form lumena when grown in Matrigel, are restored to a normal morphogenic program when transfected with CEACAM1-4S, the short cytoplasmic isoform of CEACAM1 that predominates in breast epithelia. During the time course of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
188
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 159 publications
(206 citation statements)
references
References 33 publications
16
188
1
Order By: Relevance
“…Notably, the importance of CEACAM in regulating apoptosis has been studied in various nongranulocytic cell types, and it has been found that CEACAM5 and CEACAM6 inhibit apoptosis [22], whereas CEACAM1 and CEACAM3 can induce apoptosis [20,23]. We therefore critically examined the apoptotic rate in PMN using three independent approaches: DNA fragmentation by PI staining, double-staining for annexin V and PI, and analyses of caspase-3 activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the importance of CEACAM in regulating apoptosis has been studied in various nongranulocytic cell types, and it has been found that CEACAM5 and CEACAM6 inhibit apoptosis [22], whereas CEACAM1 and CEACAM3 can induce apoptosis [20,23]. We therefore critically examined the apoptotic rate in PMN using three independent approaches: DNA fragmentation by PI staining, double-staining for annexin V and PI, and analyses of caspase-3 activity.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-CEACAM1 antibodies and soluble recombinant CEA-CAM1-Fc fusion proteins are able to mimic these interactions [11,14]. Binding of these ligands to CEACAM1 induces signaling cascades which regulate cell proliferation [11], tumor growth [15], angiogenesis [16], differentiation of dendritic cells [17], T cell cytotoxicity [18], T cell-and B cell-mediated immune responses [12,19] and apoptosis [20]. Despite progress in the study of the functions of CEACAM1, its role in regulating the fate of granulocytes is still poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…A role of CEACAM1 has also been demonstrated in the morphogenesis and lumen formation of the human breast and transfection of MCF7 breast cancer cells with CEACAM1-4S induces massive apoptosis (Huang et al, 1999;Kirshner et al, 2003). Moreover, transient expression of CEACAM1-4L in MCF7 leads to rapid cell decay (unpublished data).…”
Section: Activation and Processing Of Ceacam1 During Apoptosis S Nittmentioning
confidence: 93%
“…CEACAM1 plays an important role in the morphogenesis in human breast tissues where it is associated with apoptosis in differentiating epithelial cells (Huang et al, 1999;Kirshner et al, 2003). We recently demonstrated that crosslinking of CEACAM1 on the cell surface of tumour cells mediates apoptosis (Nittka et al, 2004).…”
Section: Introductionmentioning
confidence: 93%
“…The 14-aa-short cytoplasmic domain lacks Tyr residues, but can be phosphorylated by protein kinase C on Ser and Thr residues (11) and binds calmodulin (CaM) (11) and both actin and tropomyosin (12). Recently, we have shown that CEACAM1-4S reverts breast cancer epithelial cells to a normal morphology and mediates lumen formation in a three-dimensional culture (13).…”
mentioning
confidence: 99%